Empowering communities in Zimbabwe - new configurations of power - Campbell, Bruce M.; Sithole, B.; Nemarundwe, N. (Center for International Forestry Research, 2000)
Moves to empowering communities are now widespread in Zimbabwe. In this paper what happens to the locus of power during empowerment is discussed by drawing on case study material from three areas: Gokwe, Chivi, and Sengwe/Chikwarakwara. These areas differ in the types of resources that are important and the stakeholders involved. In Gokwe and Sengwe/Chikwarakwara the high value timber and wildlife resources, respectively, are dealt with by the rural district council (RDC) and the private entrepreneurs. Empowerment in these cases has meant rise in power of the RDC, and there are numerous examples of where the RDC is in conflict with local people. With lower value resources, the entrepreneurs are more likely to be community members, and any power struggles take place at the local level, highlighting the differences among rich and poor, traditional and modern local structures, etc. The cases illustrate that the concept of ‘community-based’ is extraordinarily difficult to achieve.